Between the Culture and Barbarians: Semiotic Analysis of the Poem „Venetian Mask...“ by Giedrė Kazlauskaitė - Sadauskaitė-Varnelė, Karolina (Semiotika, 2021)
This article presents the semiotic analysis of Giedrė Kazlauskaitė poem Venecijietiška kaukė… The research aims to delve into the structures of the poetic world of Giedrė Kazlauskaitė, which is achieved through executing a detailed semiotic analysis of one poem. Accordingly, this paper follows the semiotic framework of the analytical trajectory, which encompasses the analysis through the means of discursive, narrative, and logical semantic levels. In addition, the study includes Yuri Lotman’s discourse of the concept of the mirror in cultural semiotics. Findings derived from the semiotic analysis suggest that the figures of the mask and the mirror become central representations at the discursive level of the poem, as they exist in a paratopic space - the make-up room. The mask and the mirror appear in Kazlauskaitė’s poetry as an essential tool for shaping one’s own identity. Moreover, the analysis of the poem is supplemented with the expression of the passions of anger and jealousy. Such approach highlights two different forms of anger: destruction arising from jealousy and a creative act. These forms suggest that the passion of anger drives the subject to the act of doing. Furthermore, in this poem, the figure of the poet is not presented as calm or accommodating, but rather as angry and unafraid to show contempt.
Keywords: semiotic analysis; mask; passions; polemic structure; mirroring